Medical Biochemistry - Baynes, John W.; Dominiczak, Marek H. (Mosby, 2009)
This textbook presents human biochemistry in a physiological, rather than a chemical perspective, so it provides medical students with a clinically relevant text. The essential basic science is presented emphasising organ biochemistry.